Relationship between Experts and Enterprises Viewed via the IFRS Application: An Empirical Study in Vietnam - Anh, Tu Chuc; Thị, Ngoc Bùi; Tú, Oanh Lê Thị (Asian Economic and Financial Review, 2019)
In this research paper, the dominance of fiscal policy variables (government expenditure, total revenue, and total investment) on output in Bangladesh has been examined. The study embraces the output accounting framework where significant fiscal variables are considered that can influence economy robustly. The analysis is executed by using time series framework and holding yearly data from 1994 to 2017. The study uses augmented dickey fuller test (ADF) to check the unit root problem in the data. The result shows all data exempt unit root problem at first difference and Johansen cointegration test confirms at least two variables as cointegrated. The study applies vector error correction model (VECM) to find out both short run and long run relationship between gross domestic product, government expenditure, tax revenue and investment. No distinct relationship between any variable in the short run has been found. The result confirms a positive relationship between gross domestic product and tax revenue as well as investment. There exists a negative relationship between government expenditure and gross domestic product. The study recommends planning total tax revenue by strengthening and modernizing customs administration, tax exemptions, reducing government expenditure and inviting foreign investments.